COLIFORM MOST PROBABLE NUMBER (MPN) WITH VARIETIES OF MEDIA VOLUME LACTOSE BROTH SINGLE STRENGTH (LBSS) AND LACTOSE BROTH DOUBLE STRENGTH (LBDS) - Yunan Jiwintarum; Agrijanti Agrijanti; Baiq Lilis Septiana (poltekkes kemenkes mataram, 2017)
Most Probable Number (MPN) is a test that detects the fermentative nature of Coliform in the sample. The MPN test consists of three stages: presumptive test, confirm test, and completeness test. Each of these tests used LBSS, LBDS and BGLB media with volume between 5 ml - 10 ml. There is the variation of this media volume, whether it will affect the positivity value and MPN value of Coliform, it is a problem that will be answered in this study. The research objective was to find out the influence of media volume variation to the result of Coliform bacterium counting test method of MPN variety 5 1 1. The media volume which was varied namely LBSS and LBDS with volume variation 4 m, 6 ml, 8 ml, 10 ml, 12 Ml. The research was an experimental in laboratory. The sample was the suspense of Escherichia coli bacteria which are equivalent to standard 0.5 Mc. Farland and diluted 1000 ml sterile aquadest, the result data indicated MPN value was obtained, then it is analyzed by descriptive analysis. The findings indicated that the volume of LBDS and LBSS media were 4ml, 6ml, 8ml, 10ml, 12ml, replicated 5 times obtained positive result on all tubes 5 1 1 with MPN value> 265/100 ml. The conclusion of the research is media volume of LBSS and LBDS does not affect the positive and MPN Coliform values.